Megalencephaly syndromes associated with mutations of core components of the PI3K‐AKT–MTOR pathway: PIK3CA, PIK3R2, AKT3, and MTOR. Issue 4 (23rd August 2019) - Dobyns, William B.; Mirzaa, Ghayda M.
Abstract: Megalencephaly (MEG) is a developmental abnormality of brain growth characterized by early onset, often progressive, brain overgrowth. Focal forms of megalencephaly associated with cortical dysplasia, such as hemimegalencephaly and focal cortical dysplasia, are common causes of focal intractable epilepsy in children. The increasing use of high throughput sequencing methods, including high depth sequencing to more accurately detect and quantify mosaic mutations, has allowed us to identify the molecular etiologies of many MEG syndromes, including most notably the PI3K‐AKT‐MTOR related MEG disorders. Thorough molecular and clinical characterization of affected individuals further allow us to derive preliminary genotype–phenotype correlations depending on the gene, mutation, level of mosaicism, and tissue distribution. Our review of published data on these disorders so far shows that mildly activating variants (that are typically constitutional or germline) are associated with diffuse megalencephaly with intellectual disability and/or autism spectrum disorder; moderately activating variants (that are typically high‐level mosaic) are associated with megalencephaly with pigmentary abnormalities of the skin; and strongly activating variants (that are usually very low‐level mosaic) are associated with focal brain malformations including hemimegalencephaly and focal cortical dysplasia. Accurate molecular diagnosis of these disorders is undoubtedly crucial to more optimally treat children with these disorders using PI3K‐AKT–MTOR pathway inhibitors.